Preventing misdiagnosis in amniotic band sequence: a case report - Cristiane Rúbia Ferreira; Cibelle Freitas Pinto Lima; Ana Maria Andrello Gonçalves Pereira de Melo (University of São Paulo, 2013)
Amniotic band sequence (ABS) is an uncommon and heterogeneous congenital disorder caused by entrapment of fetal parts by fibrous amniotic bands, causing distinctive structural abnormalities involving limbs, trunk, and craniofacial regions. The incidence ranges between 1/1200 and 1/15,000 live births, but is higher in stillbirths and previable fetuses. The intrinsic theory attributes the constriction band syndrome as an inherent development defect of embryogenesis while the extrinsic theory proposes that an early amnion rupture is responsible for the adherent bands. It is also suggested that amputations and constriction rings might be due to vascular disturbances. Anomalies resulting from amniotic bands are quite variable and sometimes may simulate chromosomal abnormalities. The authors report a case of a 36-week-gestation male neonate who lived for 29 hours after a vaginal delivery with an Apgar score of 8/9/9. The mother was primipara, and the prenatal was uneventful except for two episodes of urinary tract infections. The newborn examination depicted multiple anomalies characterized by exencephaly, bilateral labial cleft with distorted nostrils and palate cleft. There was also facial skin tag band, exophthalmos with hypoplasia of the eyelids. The limbs showed distal amputation of the fingers in both hands and feet, oligodactyly associated with syndactyly in the left foot, ring constriction in the right leg, the presence of right hyperextension, and clubfoot. The upper limbs showed length discrepancies. Karyotype analysis was normal at 46 XY. The authors conclude that the recognition of the malformations secondary to ABS is important in genetic counseling to prevent misdiagnosis between chromosomal and secondary disruption disorders.